Sudan Rural Household Survey 2023: Sampling and implementation procedures for the first round - Kirui, Oliver K.; Ahmed, Mosab O. M.; Taffesse, Alemayehu Seyoum; Abushama, Hala; Siddig, Khalid (International Food Policy Research Institute, 2024)
This paper describes the data collection methodology for the 2023 Sudan Rural Household Survey (SRHS), the first nationwide survey of rural households in Sudan following the eruption of violent conflict in April 2023. The SRHS, which was conducted by the International Food Policy Research Institute in collaboration with the United Nations Development Program and the World Food Program, represents a significant effort to understand the dynamics of rural households in Sudan during a period of profound national conflict. The survey focuses on several critical themes central to household welfare, including food security, coping strategies, employment and income, livelihoods, assets, market access, and exposure to shocks. Analysis of the survey data can provide comprehensive insights into the resilience of and challenges faced by rural communities in Sudan. Computer-assisted telephone interview (CATI) methods were used to navigate the challenges of data collection in a conflict setting. The use of CATI demonstrated the adaptability and potential of innovative research methodologies in conflict-affected regions. The survey, the first round in a planned panel survey program, aims to establish a baseline of rural life, economic activities, and food security in Sudan. Panel survey data offers invaluable information to counter several analytical biases inherent to the conclusions drawn from other data structures. Subsequent rounds of the SRHS are planned for the second and fourth quarters of 2024.